Employee English and Communication Skills in Improving the Performance of Shariah Hotels in Indonesia - Regina Niken Wilantari; Imro’atul Husna Afriani (MediaTrend, 2022)
This study tested foreign language skills, especially in English, communication skills and education of more than 120 employees from 17 Islamic hotels in Indonesia with the random sampling method of selecting samples which were tested through the English language proficiency test using the experience test method which was carried out in a period of years. Month 1 of 2015 to month 1 of 2020. Test results are measured on a Likert scale. They are aggregated and compared with hotel performance collected from more than 150 annual reports from all sharia hotels in Indonesia listed on the Indonesia Stock Exchange, magazines, scientific articles, and books for 2015 to 2020. Use content analysis using the English for Specific Purposes (ESP) method. Providing insights about ESP aims to improve hotel employees' performance to facilitate communication in serving foreign guests. In researching this data, we triangulated the results of the analysis content carried out. We used the quantitative method Vector Error Correction Model to triangulate the qualitative conclusions that we used by analyzing the estimated results of employee responses in communication skills and effective survival in generating profits in the sharia hotel business listed in Indonesia stock exchange with a note that it can improve the financial performance of Islamic hotels from 2015 to 2019. We found that Islamic hotel employees' English language skills can boost the financial performance of business organizations in the Islamic hotel industry in Indonesia.